Vaccination following the expanded programme on immunization schedule could help to reduce deaths in children under five hospitalized for pneumonia and severe pneumonia in a developing country - Shahid, Abu Sadat Mohammed Sayeem Bin; Rahman, Ahmed Ehsanur; Shahunja, K. M.; Afroze, Farzana; Sarmin, Monira; Nuzhat, Sharika; Alam, Tahmina; Chowdhury, Fahmida; Sultana, Mst Shahin; Ackhter, Mst Mahmuda; Parvin, Irin; Saha, Haimanti; et al. (Frontiers in Pediatrics, 2023)
Background Worldwide, pneumonia is the leading cause of mortality in children under the age of five. An expanded program on immunization (EPI) is one kind of evidence-based tool for controlling and even eradicating infectious diseases. Objectives This study aimed to explore the impact of EPI vaccination, including BCG, DPT-Hib-Hep B, OPV, IPV, and PCV-10, among children from the age of 4 to 59 months hospitalized for pneumonia and severe pneumonia. Additionally, we evaluated the role of 10 valent pneumococcal conjugate vaccines alone on clinical outcomes in such children. Methods In this retrospective chart review, children from the age of 4 to 59 months with WHO-defined pneumonia and severe pneumonia admitted to the Dhaka Hospital of the International Centre for Diarrheal Disease Research, Bangladesh (icddr,b) between August 2013 and December 2017 who had the information on immunization as per EPI schedule by 4 months of age were included in the analysis. A comparison was made between the children who were fully immunized (immunization with BCG, DPT-Hib-Hep B, OPV, and IPV from 2013 to 2015 and PCV-10 from 2015 to 2017) and who were not immunized (consisting of partial immunization and no immunization) during the study period. Results A total of 4,625 children had pneumonia and severe pneumonia during the study period. Among them, 2,605 (56.3%) had received the information on immunization; 2,195 (84.3%) were fully immunized by 4 months of age according to the EPI schedule and 410 were not immunized. In the log-linear binomial regression analysis, immunization of children from 4 to 59 months of age was found to be associated with a lower risk of diarrhea (p = 0.033), severe pneumonia (p = 0.001), anemia (p = 0.026), and deaths (p = 0.035). Importantly, the risk of developing severe pneumonia (1054/1,570 [67%] vs. 202/257 [79%], p < 0.001) and case-fatality rate (57/1,570 [3.6%] vs. 19/257 [7.4%], p = 0.005) was still significantly lower among those who were immunized with PCV-10 than those who were not. Conclusion Children immunized as per the EPI schedule were at a lower risk of diarrhea, severe pneumonia, anemia, and death, compared to unvaccinated children. In addition, PCV-10 was found to be protective against severe pneumonia and deaths in vaccinated children. The overall results underscored the importance of the continuation of immunization, scrupulously adhering to the EPI schedule to reduce the risk of morbidities and mortalities in children, especially in resource-limited settings.